Impact of obstructive sleep apnoea/hypopnoea and its treatment with continuous positive airway pressure on the outcome of stroke - Hsu, Chung-Yao (The University of Edinburgh, 2006)
BACKGROUND: The prevalence of sleep-disordered breathing (SDB) in stroke is high. One study showed SDB had a negative impact on the functional capacity of stroke patients on discharge and another that SDB was associated with a higher mortality rate. However, these findings are disputed. The impact of SDB in stroke patients on cognition and health-related quality of life is also not clear. The one randomized controlled trial of nasal continuous positive airway pressure (CPAP) in stroke patients with SDB showed CPAP improved wellbeing but not other outcomes. I hypothesised that: (1) SDB is related to stroke outcome and (2) treatment of SDB in stroke patients with CPAP would improve functional outcome. METHODS: There are three parts of the thesis: (1) a study of the prevalence of SDB after stroke; (2) a randomized controlled trial (RCT) of CPAP after stroke and (3) a longitudinal cohort study to investigate the impact of SDB on outcome after stroke. On day 14-19 after stroke, recruited patients underwent a limited sleep study using a validated system (Embletta PDS, Medcare Flaga, Iceland). Baseline assessments were performed on the morning following the sleep study. On day 21-25 following stroke, patients who had (A+H)-h⁻¹ ≥ 30 with < 30% of central events were randomized to 8 weeks of CPAP treatment with Autoset T (ResMed, SanDiego USA) or conservative treatment for SDB. All outcomes were recorded in the 8th week after randomization or 3 months after stroke for non-randomized patients. All recruited patients received follow-up at six months after stroke. If available, patients also received 12 months and 18 months follow-up until the last recruited patient had had his 6 months follow-up. The Nottingham Extended ADL Index (EADL) was chosen as the primary outcome measure. Secondary outcome measures included: Subscales of EADL, NIH Stroke Scale (NIHSS), Barthel Index (BI), Stanford Sleepiness Scale (SSS), Addenbrooke's Cognitive Examination (ACE) and Mini- Mental State Examination (MMSE), Hospital Anxiety and ...